Emerging Pests of Horticultural Crops in Northeast and its Management - Ningombam, Arati; Akoijam, Romila; Beemrote, Aruna; Ningthoujam, Ajit Kumar; Thokchom, Sushmita; Sharma, Susheel Kumar (Indian Horticulture, 2024)
The horticulture sector is a shining beacon making a vast contribution to the rapidly growing Indian Economy. It supports the sustainable livelihood of many fruit and vegetable farmers. In addition, it also provides employment opportunities through post-harvest value addition to SHGs, entrepreneurs, rural youth, women, etc., across the country. The NE region is home to many unique and underutilised fruits and vegetables, besides many GI-tagged fruits, cash crops and spices. It contains over one-third of the country’s total fruit diversity. Such a wide range of economically important horticultural crops are infested by various insect pests,hampering their production and lowering their productivity. Changing climate and cultural practices are a few factors leading to the emergence of many insect species as pests causing economic damage. They include invasive insects alien to the country that could threaten the biodiversity of the region and are polyphagous, capable of feeding on new hosts. Since the NE region is promoted as an organic hub of the country, thrust is given to organic pest management practices to manage these pests.